2016
DOI: 10.1016/j.bbrep.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Complement-dependent and -independent aquaporin 4-antibody-mediated cytotoxicity in human astrocytes: Pathogenetic implications in neuromyelitis optica

Abstract: BackgroundNeuromyelitis optica (NMO) is an inflammatory disease caused by the aquaporin (AQP)-4-antibody. Pathological studies on NMO have revealed extensive astrocytic damage, as evidenced by the loss of AQP4 and glial fibrillary acidic protein (GFAP), specifically in perivascular regions with immunoglobulin and complement depositions, although other pathological patterns, such as a loss of AQP4 without astrocyte destruction and clasmatodendrosis, have also been observed. Previous studies have shown that comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
(30 reference statements)
0
20
0
Order By: Relevance
“…The fluorescence intensity analysis showed that only cells with high deposition of C5b-9 (high signal in ICC analysis) had decreased expression of GFAP (10% of all astrocytes), whereas the rest of astrocytes were characterized by low C5b-9 deposition and normal GFAP expression, comparable to astrocytes incubated with HC or RRMS serum (Figure 3 C, green/red arrows). These findings showed that the majority astrocytes are resistant to AQP4-C hu -induced destruction, probably due to their membrane expression of complement inhibitory protein CD59 ( 8 , 27 ), or sublytic C5b-9 concentration ( 28 ), suggesting that another parallel mechanism of astrocyte destruction in NMOSD inflammation should exist.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The fluorescence intensity analysis showed that only cells with high deposition of C5b-9 (high signal in ICC analysis) had decreased expression of GFAP (10% of all astrocytes), whereas the rest of astrocytes were characterized by low C5b-9 deposition and normal GFAP expression, comparable to astrocytes incubated with HC or RRMS serum (Figure 3 C, green/red arrows). These findings showed that the majority astrocytes are resistant to AQP4-C hu -induced destruction, probably due to their membrane expression of complement inhibitory protein CD59 ( 8 , 27 ), or sublytic C5b-9 concentration ( 28 ), suggesting that another parallel mechanism of astrocyte destruction in NMOSD inflammation should exist.…”
Section: Resultsmentioning
confidence: 92%
“…However, only a small subset (~10–11%) of cultured astrocytes was lysed and demonstrated GFAP loss as a result of C5b-9 formation, even though all astrocytes were opsonized by IgG1. This might be a result of membrane expression of complement regulatory proteins on astrocyte surface ( 27 , 28 ) or sublytic concentration of C5b-9 ( 28 ). Postmortem histological analysis revealed that in normal human brain, opposite to other organs, astrocytes are devoid of CD46 (membrane cofactor protein), CD55 (decay accelerating factor), or CD59 (protectin) that inhibit activation of the C hu cascade ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…AQP-4 antibody has been reported to be expressed in the brain (Badaut et al, 2007); it is the most abundant water channel in the brain (Rash et al, 1998) and controls brain water homeostasis (Nielsen et al, 1997). Amassing reports (Misu et al, 2013;Nishiyama et al, 2016;Yick et al, 2018) have shown that AQP-4 can induce complement independent pathologies. Experimental reports have shown that inflammatory sequela follows the binding of NMO-IgG to AQP-4 (Hinson et al, 2012;Pittock et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Beside the higher sensitivity to tissue microstructure of the sADC over the ADC, such discrepancy could possibly result from the modified astrocyte phenotype associated with a long-term inhibition of AQP4 expression found in those previous studies [46]. The sub-acute or chronic inhibition of AQP4 activity by AQP4-antibodies or small interfering RNA duplexes alter astrocyte morphology and decrease water permeability [47,48] which could result in an ADC decrease. Also, the effects we observed in baseline conditions should be distinguished from those obtained in conditions of neuronal activation for which AQP4 inhibition by extracellular acidification results in astrocyte swelling, capillary lumen expansion and Virchow-Robin space reduction [49].…”
Section: Discussionmentioning
confidence: 99%